2017
DOI: 10.4103/jnrp.jnrp_482_16
|View full text |Cite
|
Sign up to set email alerts
|

Does Gender Influence Electroconvulsive Therapy Sessions Required across Psychiatric Diagnoses? A 5-Year Experience from a Single Center

Abstract: Context:There is a paucity of systematic data reflecting the practice of electroconvulsive therapy (ECT) from developing countries.Aim:We aimed to identify the number of ECT sessions required to yield response and gender diffeferences in the number of sessions across various diagnostic categories.Setting and Design:A record-based study from a teaching cum tertiary care hospital in South India.Subjects and Methods:Case records of patients who received modified ECT from January 2011 to January 2016 were reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 19 publications
1
15
1
Order By: Relevance
“…About three-fourths of our study inpatients were covered by public insurances. Our results are supported by past studies that found ECT was used for mood disorders predominantly in females (65.2%) than in males, and one-third of ECT recipients were aged 65 years and older and more than half of the population is covered by Medicare [12][13][14][15]. Several factors may be relevant to higher utilization of ECT in the geriatric population, like patients have a lower tolerance to medication owing to age-associated pharmacokinetic changes and increased sensitivity to psychotropic medications [13].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…About three-fourths of our study inpatients were covered by public insurances. Our results are supported by past studies that found ECT was used for mood disorders predominantly in females (65.2%) than in males, and one-third of ECT recipients were aged 65 years and older and more than half of the population is covered by Medicare [12][13][14][15]. Several factors may be relevant to higher utilization of ECT in the geriatric population, like patients have a lower tolerance to medication owing to age-associated pharmacokinetic changes and increased sensitivity to psychotropic medications [13].…”
Section: Discussionsupporting
confidence: 90%
“…Our results are supported by past studies that found ECT was used for mood disorders predominantly in females (65.2%) than in males, and one-third of ECT recipients were aged 65 years and older and more than half of the population is covered by Medicare [ 12 - 15 ]. Several factors may be relevant to higher utilization of ECT in the geriatric population, like patients have a lower tolerance to medication owing to age-associated pharmacokinetic changes and increased sensitivity to psychotropic medications [ 13 ]. A national register-based observational study from Sweden found that ECT for BD was associated with high response rates compared to those treated by psychotropic medications and the strongest prognostic factor being “high age” and absence of psychiatric comorbidities [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…These regions include subcallosal cingulate, ventral anterior internal capsule, and ventral striatum, which are all involved in regulation of mood and antidepressant response [150,151]. Existing evidence is limited, a few studies using these neuromodulatory approaches have found equivalent efficacy in both males and females [152,153]. However, response to TMS may be modulated by hormone levels as response in premenopausal women was correlated with estradiol/ progesterone ratio while postmenopausal women were the least responsive to treatment [154].…”
Section: Fast Acting Antidepressantsmentioning
confidence: 99%
“…Considering the studies in the literature evaluating the ECT responses of male and female psychiatric patients, the generally accepted approach is that there is no difference in response rates between genders. In a retrospective study in which Manohar et al 11 examined the gender differences in the number of ECT sessions required for response to treatment, the mean number of ECT sessions was 9.7 ± 6.1 in the schizophrenia group (n = 43) and 7.3 ± 3.8 in the affective disorder group (n = 82). 11 While the number of sessions was significantly different in terms of diagnoses, no difference was found in terms of gender.…”
Section: Discussionmentioning
confidence: 99%
“…13 In a retrospective study to examine the gender differences in the number of ECT sessions required for response to treatment, a significant difference was found out in terms of diagnoses while there was no difference in terms of gender. 11…”
Section: Introductionmentioning
confidence: 99%